Analysis of Social Network Data, Possible "Show and Tell" Projects - Faust, Katherine (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Each person is expected to give brief social network analysis "show and tell" presentations on four occasions during the quarter. These will take place during the first part of class and may be in any reasonable format. The list below gives some things you might do and approximate weeks when you might do them. You are welcome to do other kinds of network analyses that are not listed below.